PEMETAAN LAHAN POTENSIAL BUDIDAYA LAUT IKAN KERAPU BEBEK Cromileptes Altivelis DI DESA PEMUTERAN, KECAMATAN GEROKGAK, KABUPATEN BULELENG, BALI - Hendra Yoga Pratama; I Dewa Nyoman Nurweda Putra; Ni Luh Putu Ria Puspitha (Journal of Marine Research and Technology, 2019)
The potential of aquaculture in Indonesia is very large, especially fish and mollusks. Around 1.052.720 ha total potential sea area for fish cultivation such as snapper, beronang, and grouper. One potential that needs to be developed in the field of fisheries is duck grouper (Cromileptes altivelis). One area in Indonesia especially in Bali, which conducting marine aquaculture using floating net cage system is Pemuteran Village, Gerokgak District, Buleleng Regency, Bali. This study aimed to determine the right information and improve the potential of the tap nets for the activity of duck grouper at Pemuteran Village level can be done with floating net cage system. In this study three stages were carried out, namely interpolation, reclassification, and overlay. Based on the result of overlay of all spatial information, a potential map for the activity of duck grouper cultivation with KJA system is divided into 2 conformity classes, namely: S1 for the appropriate category (very suitable), S2 (quite appropriate category ) and T (for not suitable category). Based on the map in figure (3), it shows that suitable results for agriculture in Pemuteran village indicate that proper resources for aquaculture are in the right system KJA is Very suitable (S1) of 1,67 km2, quite appropriate (S2) of 6,25 km2 and not suitable (T) of 1,31 km2.